2021
DOI: 10.1001/jamanetworkopen.2021.33199
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Discrimination, Bias, and Inclusion in a United States Hematology and Oncology Fellowship Program

Abstract: IMPORTANCEMedical trainees frequently experience discrimination. Understanding their experiences is essential to improving learning environments. OBJECTIVE To characterize trainee experiences of discrimination and inclusion to inform graduate medical education (GME) policies. DESIGN, SETTING, AND PARTICIPANTS This qualitative study used an anonymous telephone interview technique to gather data from hematology and oncology fellows. All current trainees and recent graduates were eligible. Interviews were conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…A salient perception by non-US IMGs was the need to assimilate to the dominant culture and hinder self-expression to build rapport and improve evaluations. Participants felt penalized for behaviors deemed appropriate in their home culture, which is unfortunately consistent with prior reports 9 , 14 , 38 and probably stems from the lack of cultural competence in healthcare. 39 , 40 A specific example is the negative feedback for lack of assertiveness mentioned by our participants, which has been reported by ethnically diverse medical students, 41 as well as female resident physicians.…”
Section: Discussionsupporting
confidence: 76%
“…A salient perception by non-US IMGs was the need to assimilate to the dominant culture and hinder self-expression to build rapport and improve evaluations. Participants felt penalized for behaviors deemed appropriate in their home culture, which is unfortunately consistent with prior reports 9 , 14 , 38 and probably stems from the lack of cultural competence in healthcare. 39 , 40 A specific example is the negative feedback for lack of assertiveness mentioned by our participants, which has been reported by ethnically diverse medical students, 41 as well as female resident physicians.…”
Section: Discussionsupporting
confidence: 76%
“…Discrimination is a major issue in US GME as it seems that the focus is entirely on the assimilation of the new culture without an appreciation of being different [39]. This phenomenon is seen in all levels of the US HCS, from patients and family members to colleagues and superiors, adding that IMGs have been historically confined to less-desirable specialties and locations [26].…”
Section: Racial Discriminationmentioning
confidence: 99%
“…Interviews led by investigators of a fellowship program revealed that not only foreign graduates but also USMG treated as a foreigner (for having accent) are subject to racism [39]. In many cases, discriminatory behavior comes from patients [27], and these events are rarely conveyed to authorities either because offended residents are not aware of policies for reporting patient discrimination or concerned about retaliation [39].…”
Section: Racial Discriminationmentioning
confidence: 99%
See 1 more Smart Citation
“…Trainees and junior faculty from UIM groups often face hostile environments during training and after they have joined the oncology workforce, including daily microaggressions, exclusion from leadership positions, and not receiving the appropriate mentorship and sponsorship. [82][83][84] It is often believed that Latinx/Hispanic trainees and faculty should be mentored by faculty or leaders with the same cultural or ethnic backgrounds. However, as described in several sections of this article, there are not enough senior Latinx/ Hispanic faculty to mentor the new generation of oncologists.…”
Section: Individual Efforts To Improve Representation and Inclusionmentioning
confidence: 99%